Collaborative Governance dalam Pengelolaan Bumdes sebagai Upaya Penguatan Ekonomi Desa di Kabupaten Klaten - Vindi Octaviani (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2022)
Village Ministerial Regulation, the Development of Rural Area and Migrator No. 1 of 2015 confirms the guidelines on village owned enterprises (BUMDes) to emphasize village authority in developing village economics with a business entity. The establishment of BUMDes is expected to be able to improve the community's economic level and increase Village Original Income (PADes). From 2014 to the latest data in December 2020, Klaten Regency experienced a rapid increase in the number of BUMDes. From 33 BUMDes to 364 BUMDes. However, the rapid establishment of BUMDes is not accompanied by its management, which is evidenced by the low proportion of BUMDes in the advanced category. This paper aims to map the roles of actors, strategies for developing BUMDes and how to overcome challenges in its implementation in managing BUMDes in BUMDes Tirta Mandiri and BUMDes Janti Jaya. The research was conducted using an exploratory qualitative method and will be analyzed through 3 stages from Stephan Balogh, namely system context, drivers and dynamics of collaboration. The involvement of the village government and the community affects the development of BUMDes. The condition of abundant natural resources supports BUMDes in terms of natural resources but still needs training and development to get qualified human resources who are not only able to manage BUMDes but can also develop and bring BUMDes able to overcome various challenges.Keywords: BUMDes, collaboration, collaborative governance, management, village